Legal analysis of state support for compatriots abroad enshrined in Kazakhstan - ONGARBAYEV, Y.A; NURMAGAMBETOV, A.M; ZHARKENOVA, S.B; GALIAKBAROVA, G.G (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The goal of this article was to study the problematic of legal regulation of state support for the compatriots abroad. The authors applied general scientific methods, as well as special techniques and for studying phenomena and processes. The issues of state support for compatriots abroad, primarily the Kazakh diaspora, were examined from different perspectives. The research results included the consideration of the most positive aspects of legal regulation of support for compatriots, and the development of proposals to be included in the first draft bill in the history of modern Kazakhstan. RESUMEN El objetivo de este artículo fue estudiar los problemas de la regulación legal del apoyo estatal para los compatriotas en el extranjero. Los autores aplicaron métodos científicos generales, así como técnicas especiales para estudiar fenómenos y procesos. Los temas de apoyo estatal para compatriotas en el extranjero, principalmente la diáspora kazaja, fueron examinados desde diferentes perspectivas. Los resultados de la investigación incluyeron la consideración de los aspectos más positivos de la regulación legal del apoyo a los compatriotas, y el desarrollo de propuestas para ser incluidas en el primer proyecto de ley en la historia de la Kazajstán moderna.